A justiça restaurativa na política de socioeducação: concepções, crítica e possibilidades - Amorim, Tâmara Ramalho de Sousa (2018)
The present thesis aims to analyze the Restorative Justice (RJ) within the scope of the Socioeducation Policy. According to its most widely used concept, JR can be understood as the process by which the parties involved in a specific offense collectively resolve how to deal with the consequences of the offense and its future implications. It is assumed, in this thesis, that: Restorative Justice is situated in a context of partnership between State and civil society; in the policy of Socioeducation RJ enters through the justice system, characterizing a response of the State to the issue of the infraction, through consensus; in considering crime as a violation of people and relationships, RJ presents an interpersonal approach, not provoking structural transformations; despite this, the RJ may present itself as a counter-hegemonic possibility, representing a tool that provides young users of the Socioeducation Policy with listening and participation. Based on these assumptions, it is argued that Restorative Justice in SocioEducation Policy is characterized as a response of the State through consensus and epistemological basis in interpersonal relations, revealing an instrument of guarantee of rights, as the right to participate. Based on a critical perspective, the theoretical categories Social Policy and Restorative Justice were used. Regarding the method, the thesis research was carried out in six Brazilian municipalities, in the north, northeast, south and center-west regions. Twenty professionals working with RJ participated in the research in the scope of socioeducational policy. As instrument, semi-structured interviews were used, recorded, transcribed and submitted to analysis with the help of MaxQDA software. The results of the interviews were organized in three categories: Restorative Justice, Restorative Justice as Public Policy and Restorative Justice in Socioeducation. Overall, the data points to the existence of RJ’s understanding as a new conception of justice. The predominant theoreticalepistemological perspective elucidated the focus on interpersonal relations. The justice system has been identified as the main actor in relation to the RJ as public policy, participating in both the implementation and execution of the policy, seeming to represent an instrument of the State in the consensus articulation. However, the State's actions were also identified in partnership with civil society, represented, for example, by non-governmental organizations. With regard to Socioeducation, the data pointed out that RJ practices are used in the community, in the judicial context and in the execution of socioeducational measures. The most commonly used restorative practice are peacebuilding circles, restorative meetings, and conflict mediation; it has been noticed that they have been used as a new resource for acting with the young people in the socioeducation process, which allows reception and listening. In view of the results, the thesis is confirmed that Restorative Justice in socioeducational policy is characterized as a response of the State that has epistemological basis in interpersonal relations, revealing an instrument of guarantee of rights, such as to participate.